Hubungan Pengetahuan Tentang Alat Pelindung Diri Terhadap Perilaku Penggunaan Alat Pelindung Diri Pada Tim SAR Di Soloraya - Alvinda Radya Bagaskara; Sheena Ramadhia Asmara Dhani (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Personal Protective Equipment (PPE) is a tool used to protect the body from the risk of work accidents. Technically, this tool can reduce the severity of injuries. PPE does not eliminate the source of danger, but limits contact with the danger by providing a barrier. This study, which uses a cross-sectional approach, aims to determine the relationship between knowledge of personal protective equipment and the behavior of using personal protective equipment during the SAR team in Soloraya. The research sample used was 123 SAR member respondents in Soloraya covering the districts of Karanganyar, Wonogiri, Sukoharjo, and Klaten in 2025. The instrument used was GoogleForm which has been declared valid and reliable. Data analysis was carried out using the Chi-square statistical test. Univariate analysis showed that respondents with good knowledge were 90 respondents (73.2%), while those with poor knowledge were 33 respondents (26.8%). Bivariate statistical analysis showed a p-value = 0.040 (p <0.05), which means there is a significant relationship between the level of knowledge of personal protective equipment and the behavior of using personal protective equipment.